STUDI PEMAHAMAN DAN PENERAPAN STANDAR KOMPETENSI KETERAMPILAN KERJA TENAGA KERJA PADA PELAKSANAAN PROYEK KONSTRUKSI - Candra Yuliana (Universitas Lambung Mangkurat, 2009)
Head of workman and workman are the primary movers and and implementers in the implementation of a construction project. As the growth of construction projects in Banjarmasin, the head of workman and workman must have expertise in accordance with the existing standards. This is supported by National Skills Competency Standards of Indonesia which issued and determined by Department of public works for sector head of workman and workman skills. This study was conducted to determine the understanding head of workman and workman on job skills competency standards and to learn its application in construction projects in Banjarmasin. The methode which was used in this study is validity test, reliability test and descriptive analysis (average value). Result of analysis of questionnaires and interviews from 7 construction projects (90 workman dan 7 head of workman), the percentage obtained for 79,63% of understanding (mason), 88,15% (carpenter), 88,75% (blacksmith/concrete), 90,47% (head of mason), 95,92% (head of carpenter), 92,86%(head of blacksmith /concrete). For the competency standard implementation acquired job skills by applying the percentages of 33,70% (mason), 30,37% (carpenter), 27,09% (blacksmith/concrete), 14,28% (head of mason), 20,41% (head of carpenter), 26,19%(head of blacksmith/concrete). In most of the construction project head of workman and workmen understand competency standard of work skills but not followed by the implementation.